$\boldsymbol{f}$-Biharmonic and Bi-$\boldsymbol{f}$-Harmonic Submanifolds of Product Spaces - Karaca , Fatma; Özgür, Cihan (Sarajevo Journal of Mathematics, 2017)
We consider $f$-biharmonic and bi-$f$-harmonic submanifolds of the product of two real space forms. We find the necessary and sufficient conditions for a submanifold to be $f$-biharmonic and bi-$f$-harmonic in a product of two real space forms.